Confirmation of mutations in PROSC as a novel cause of vitamin B6-dependent epilepsy. Issue 12 (8th April 2017) - Plecko, Barbara; Zweier, Markus; Begemann, Anaïs; Mathis, Deborah; Schmitt, Bernhard; Striano, Pasquale; Baethmann, Martina; Vari, Maria Stella; Beccaria, Francesca; Zara, Federico; Crowther, Lisa M; Joset, Pascal; et al.
Abstract : Vitamin-B6 -dependent epilepsies are a heterogenous group of treatable disorders due to mutations in several genes ( ALDH7A1, PNPO, ALPL or ALDH4A1 ). In neonatal seizures, defects in ALDH7A1 and PNPO explain a major fraction of cases. Very recently biallelic mutations in PROSC were shown to be a novel cause in five families. We identified four further unrelated patients harbouring a total of six different mutations, including four novel disease mutations. Vitamin B6 plasma profiles on pyridoxine did not enable the differentiation of patients with PROSC mutations. All four patients were normocephalic and had normal cranial imaging. Pyridoxine monotherapy allowed complete seizure control in one, while two patients had occasional febrile or afebrile seizures and one needed additional valproate therapy for photosensitive seizures. Two patients underwent a controlled pyridoxine withdrawal with signs of encephalopathy within a couple of days. Three had favourable outcome with normal intellectual properties at age 12.5, 15.5 and 30 years, respectively, while one child had marked developmental delay at age 27 months. The clinical and electroencephalographic phenotype in patients with PROSC mutations was indistinguishable from ALDH7A1 and PNPO deficiency. We therefore confirm PROSC as a novel gene for vitamin-B6 -dependent epilepsy and delineate a non-specific plasma vitamin B6 profile under pyridoxine treatment.